2019
DOI: 10.1002/ijc.32482
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of unknown primary: Incidence rates, risk factors and survival among adolescents and young adults

Abstract: Cancer of unknown primary (CUP) is a clinical challenge especially when it occurs in adolescents and young adults (AYA), aged 15–39 years, due to the sparse data in this population. The available data has not described the population‐based epidemiological features of CUP among AYA. Therefore, we collected patient information from the Surveillance, Epidemiology and End Results (SEER) registry, 1990–2015. Age, gender, ethnic, five pathological classification groups were assessed along with an aggregate level soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…An epidemiological analysis reported that adolescents and young adults had a higher incidence of squamous cell carcinoma than the general CUP population (29% vs. 10%), which is consistent with our results. 26 Lymphatic metastasis is a relatively early process in distant metastasis and nodal metastasis for most solid tumors. Yilin et al found that the sentinel lymph node is the first stop of lymphatic spreading of CUP cases, which helps track the primary tumor, especially for well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological analysis reported that adolescents and young adults had a higher incidence of squamous cell carcinoma than the general CUP population (29% vs. 10%), which is consistent with our results. 26 Lymphatic metastasis is a relatively early process in distant metastasis and nodal metastasis for most solid tumors. Yilin et al found that the sentinel lymph node is the first stop of lymphatic spreading of CUP cases, which helps track the primary tumor, especially for well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Among histologic subtypes, adenocarcinoma was the predominant entity, but the study also included a substantial number of undifferentiated and squamous cell carcinomas. Only 12/252 (4.8%) of patients fell into the adolescent and young adults age group (15–39 years), among them nine with ≥36 years of age. The distribution of histologic subtypes in this young age cohort was comparable to the overall study cohort with adenocarcinoma as the leading subtype ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…The genetic and epigenetic aberrations in human cells are primarily attributable to the interaction of genetic and exogenous cancer risk factors ( 10 ). Cancers in children are likely linked to prenatal and congenital factors ( 11 ), with at least 10% of pediatric cancer patients harboring a germline mutation in a cancer predisposition gene ( 12 ). For instance, children with certain constitutional genetic abnormalities in the TP53 gene face an increased risk of acute lymphoblastic leukemia (ALL) ( 13 ); germline mutations in SUFU and PTCH1 have also been revealed as risk factors for infant medulloblastoma ( 14 ).…”
Section: Introductionmentioning
confidence: 99%